Benin : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper reviews the vulnerability and risks associated with Benin's banking sector. Banks in Benin show significant vulnerabilities. Although financial soundness indicators do not present immediate stability concern, the quality of banks' loan portfolio is low and has constrained credit to the private sector. Stress tests confirm that credit risk is of particular concern. Structural impediments are at the root of these risks, including problems with property titles, information asymmetries, and the weak judiciary, which complicates contract enforcement. Structural reforms and a re-calibration of fiscal policies to reduce the government's lending needs are necessary to mitigate these risks over time.